Geological Modeling of the Senonian Aquifer in the Oued Guir Watershed (Southeast Morocco) - Messaoudi Badre; Kabiri Lahcen; El Ouali Mohamed; Ait Lahssaine Ismail; Kadiri Abdelhakim; Essafraoui Badre (E3S Web of Conferences)
The Oued Guir watershed in southeast Morocco stretches widely from the High Atlas in the north to the Hamadas in the south. This basin is characterized by an arid climate strongly influenced by continental conditions. The Lower Guir has become a focal point for the development of modern agriculture following the launch of the Green Morocco Plan. This has led to increased overexploitation of groundwater, specifically the shallow Senonian aquifer. The objective of this study is to model the geological formations of the Senonian aquifer using the Geological Modeling System and GIS software, based on drillings and wells data to understand better the distribution of geological formations and hydraulic characteristics of this aquifer. The obtained geological model shows lateral and vertical variations of the facies and thickness of the Senonian formations. The facies change between clays, silts, and sands, while the thickness exceeds 650 meters. From a hydrodynamic point of view, the transmissivity of this aquifer varies between 0.11 × 10−4 and 7.2 × 10−4 m2/s, with an average of 3.65 × 10−4 m2/s. These characteristics play a crucial role as aquifers in the basin that ensure water resources of the Boudnib area.